1993
DOI: 10.1073/pnas.90.10.4748
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid beta-protein as a substrate interacts with extracellular matrix to promote neurite outgrowth.

Abstract: Progressive deposition of amyloid 3-protein In brain, whether A,B has any physiological role is unknown. Studies aimed at elucidating the biological effects of A/3 on the nervous system have yielded equivocal results. Addition of synthetic peptides corresponding to the first 28 or 42 amino acids of the Al3 sequence to culture medium resulted in a dose-dependent effect on survival and neurite outgrowth of rat hippocampal neurons (3, 4). With a similar paradigm, AP-(1-40) peptide was found to be both trophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(95 citation statements)
references
References 28 publications
9
84
1
1
Order By: Relevance
“…A similar idea was proposed by Koo et al (1993), who found that low levels of A␤ in combination with ECM proteins such as fibronectin and laminin were able to stimulate neurite outgrowth. For this reason, further studies on the effects of A␤ on ECM are needed.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…A similar idea was proposed by Koo et al (1993), who found that low levels of A␤ in combination with ECM proteins such as fibronectin and laminin were able to stimulate neurite outgrowth. For this reason, further studies on the effects of A␤ on ECM are needed.…”
Section: Discussionsupporting
confidence: 64%
“…Low amounts of A␤1-40 and A␤1-42 (0.1-1.0 ng/well) stimulate neurite outgrowth, whereas higher amounts (Ն3 g/well) inhibit neurite outgrowth. The dose dependence of the A␤ effects may explain why Koo et al (1993) found that neurite outgrowth from rat dorsal root ganglion neurons was stimulated by low amounts of substrate-bound A␤1-40 (0.5-5.0 g/cm 2 ), whereas Fraser et al (1994) reported that larger amounts of substrate-bound A␤ (ϳ1 mg/mm 2 ) inhibited neurite outgrowth from mouse neuroblastoma cells. The view that A␤ can inhibit neurite outgrowth is also supported by the studies of Tolar et al (1998), which showed that when sympathetic neurons were grown on slices of AD amygdala, neurite outgrowth was less in plaque-rich regions of the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular deposits of beta-amyloid (A␤), which accumulate in the brain in Alzheimer disease (AD) as a component of the neuritic plaque, bring about neuronal damage and dysfunction (1)(2)(3)(4)(5)(6)(7)(8)(9), and microglial activation through specific interactions with these cells (10)(11)(12)(13)(14). A␤ perturbs cellular properties by multiple mechanisms, including induction of oxidant stress, challenging cellular antioxidant defenses and redirecting protein synthesis.…”
mentioning
confidence: 99%
“…The neurotrophic effects of very low Aβ concentrations in tissue culture have been reported. 36 However, there appears to be no physiological purpose for accumulation of Aβ in the brains of AD patients. Therefore, it is assumed that removal of excess Aβ will be without negative effects.…”
Section: Functional Catalytic Ig Effectsmentioning
confidence: 99%